Validation of uterine artery embolization before surgical laparoscopic myomenucleation compared to single surgical laparoscopic myomenucleation for the treatment of large fibroids and uterus myomatosus - Hertling, Stefan; Schleußner, Ekkehard; Graul, lsabel (Frontiers in Medicine, 2023)
Aim: To determine the efficacy of preoperative uterine artery embolization (uterine artery embolization; EUA) prior to elective laparoscopic fibroid removal compared to single laparoscopic fibroid removal in women with large uterine fibroids and women with uterus myomatosus. MATERIAL AND METHODS: A total of 202 women with symptomatic uterine fibroids who were scheduled for elective fibroid enucleation were included in this retrospective, monocentric, non-randomized study. Two procedures were compared in a matched-pair analysis: women who received percutaneous UAE 24 hours prior to elective laparoscopic fibroid eviction for large uterine fibroids (greater than 6 cm) and uterus myomatosus. And women who received laparoscopic fibroid enucleation alone for large uterine fibroids and uterus myomatosus. Outcome parameters for effectiveness were the hospital stay, the operating time and the intraoperative blood loss. Results: Women who underwent preoperative percutaneous embolization of the uterine arteries, both for large fibroids and uterus myomatosus, had significantly less blood loss, shorter hospital stays, and shorter operating times. Conclusions: Especially women with uterus myomatosus can benefit from the combination therapy of preoperative percutaneous uterine embolization with subsequent laparoscopic myoma enucleation.